Rubén Darío, lo fantástico y la Revolución Mexicana - Nappo, Daniel J. (2017)
In the last years of his life, the Nicaraguan poet Rubén Darío returned to the fantastic short story because the genre offered the best narrative expression of the confusion and doubt in which he was living. In September 1910 Darío made his only visit to Mexico, which at the time was just at the beginning of the great Revolution that would overthrow the thirty-four-year-old dictatorship of Porfirio Díaz. The experience of being in the midst of a great social upheaval, as an invited guest of honor that, nevertheless, was not permitted to visit the capital, was probably an inspiration for his penultimate short story, “Huitzilopoxtli: Mexican Legend” (1977a).